Understanding the Role of Educators: Teachers’ Awareness of Character Education in Indonesia - Amrin Mushawir; Mhd. Lailan Arqam; Mgr Sinomba Rambe; Rivaldiansolih Lubis (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
Educators or teachers play a fundamental role in the field of education, not only as instructors but also as mentors in shaping students' character. Character education is an essential aspect of forming individuals with noble morals, in line with national educational goals. However, teachers' awareness of this role remains a challenge that needs attention. This study aims to raise teachers' awareness of the importance of character education in shaping students who are not only academically intelligent but also morally upright. This research employs a qualitative descriptive method with a library research approach, where data is collected through literature reviews from books, journals, and other academic sources. The findings indicate that teachers, as role models in character development, bear a significant responsibility that cannot be carried out individually. Synergy among teachers, school administrators, and other stakeholders is necessary to create an educational environment conducive to character development. Additionally, character education should be integrated into the learning process so that students achieve a balance between intellectual and moral intelligence, enabling them to face life’s challenges more effectively